RESEARCH ON MODELING METHOD OF EQUIVALENT TURNING FORCE MODEL (MT) - WU MingZhou; ZHANG GuangPeng; GOU JianFeng; ZHANG Peng (Jixie qiangdu)
In view of the low accuracy of cutting force prediction caused by the difficulty of considering the tip arc radius, the main cutting edge arc radius and the tool working angle in the traditional turning force prediction model, an equivalent turning force model considering the tip arc, the main cutting edge arc radius and the working angle based on a small amount of turning force experimental data is established in this paper. The model is a turning force equivalent model of ideal turning tool with three nonlinear equations with equivalent principal deflection angle, equivalent edge inclination angle and equivalent normal forward angle as independent variables through the turning force experimental data and coordinate transformation matrix obtained by turning once. A turning force prediction model based on the equivalent model is established. Finally, the effectiveness of the prediction model is verified by turning force experiments.